Tales of Criminal Cases : Discretion of Court in Suspension of the Execution of a Penalty or Suspension of the Sentence of a Penalty and the Conditions for Controlling the Behavior of the Offender - Krawkeo, Poranee (Mae Fah Luang University Law Journal, 2021)
Even though the provision in Article 56 of the Criminal Code in relation to the court discretion on such topics is not much taught at the undergraduate level but in practice, it is of utmost important as it also requires a discreet consideration with supporting reasons in accordance with the intendment of law, principles of criminology as well as penology. The article puts a focus on telling stories through two criminal cases in the background leaving a space at the end of the article to readers to use their discretion for a suspension of the execution of a penalty or suspension of the sentence of a penalty and setting conditions for controlling the behavior of each offender who committed similar offenses with minor differences in details. This is to allow law students to understand the principles and background concepts as well as realizing the significance of the analysis and justification process which is important for lawyers.